A Study on the Effect of Gold Nanoparticles for Dye Sensitized Solar Cell Using Hibiscus Rosa-Sinensis as Photosensitizer - Ahmad, Siti Nursyahirah; Yahaya, Nor Afifah; Bahsan, Rosnadiah; Rozali, Shaifulazuar (International Journal of Integrated Engineering, 2022)
Dye-sensitized solar cells (DSSC) mainly uses organic components as an alternative way of light harvesting element to replace the traditional silicon solar cells. Natural dye alternatively is being used as sensitizers to overcome the limitation of inorganic ruthenium dye which contains heavy metal. In this study, DSSC is expected to enhance its optical properties and light absorption by implementing gold (Au) nanoparticles. Various natural and organic sources can be extracted and acted as a photosensitizer to trap solar energy. Fresh Hibiscus Rosa-Sinensis flowers are one of the good candidates to give higher light absorption in DSSC. The characteristics of the dye photosensitizer will be observed under UV-Vis-NIR Spectrophotometer. The efficiency of complete DSSC will be determined by using LIV tester. An attempt to enhance light-harvesting efficiency and hence the light to current conversion efficiency by mixing Au nanoparticles TiO? QUOTE paste. Au nanoparticle was selected because it can act as a medium between the dye and Ti QUOTE O? to increase the electron transmission speed. The Hibiscus dye in DSSC achieved an efficiency of 0.14%. However, the efficiency reduced to 0.000178% as Au NPs was added. The effects of the addition of Au nanoparticles are discussed.